Enhanced plasmon coupling of partly embedded gold nanospheres with surrounding silicon. (19th June 2017) - Zuo, Zewen; Wen, Yibing; Zhang, Sheng; Qu, Jun; Cui, Guanglei; Shi, Yi
Abstract: Gold nanospheres (AuNSs) were partly embedded into silicon through metal-assisted chemical etching, producing multiple-dimensional coupling of the plasmon resonances with the induced image charges in the surrounding medium. Rich plasmonic features of such coupling system were revealed by single particle dark-field scattering spectra, characterizing by two splitted multipolar resonances at short wavelength region and a mixed dipolar resonance extending to infrared region. Numerical electrodynamic calculations indicated that the multipolar modes arise from the in-plane and out-of-plane quadrupolar resonances, which are excited by the horizontal and verticle electric field components, respectively, of the incident light owing to the enhanced coupling interaction. As the embedding depth increases, the degree of symmetry breaking in such nanoparticles/substrate system changes, resulting in significantly modified optical response, which supplies a new way to modulate the optical properties of plasmonic nanoparticles.